2015
DOI: 10.1002/2015wr017022
|View full text |Cite
|
Sign up to set email alerts
|

Migration behavior of supercritical and liquid CO2 in a stratified system: Experiments and numerical simulations

Abstract: Multiple scenarios of upward CO2 migration driven by both injection‐induced pressure and buoyancy force were investigated in a horizontally and vertically stratified core utilizing a core‐flooding system with a 2‐D X‐ray scanner. Two reservoir‐type scenarios were considered: (1) the terrestrial reservoir scenario (10 MPa and 50°C), where CO2 exists in a supercritical state and (2) the deep‐sea sediment reservoir scenario (28 MPa and 25°C), where CO2 is stored in the liquid phase. The core‐flooding experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 75 publications
(108 reference statements)
0
13
0
Order By: Relevance
“…the scale at which all reservoir processes operate) (Shafer, 2013). Most significantly, such developments have revealed that results must be interpreted by acknowledging the fact that capillary pressure heterogeneity results into local saturation development (Graue, 1994;Chaouche et al, 1994;Shi et al, 2011;Pini et al, 2012;Alemu et al, 2013;Oh et al, 2015;Ott et al, 2015), which may lead to apparent flow rate effects on macroscopic properties of relative permeability and residual trapping (Perrin and Benson, 2010;Krevor et al, 2011;Kuo and Benson, 2015;Reynolds and Krevor, 2015). Accordingly, improved laboratory workflows are now being developed that make use of such wealth of information by e.g., referring to the internal structure of the sample and in-situ observations, to obtain accurate parameterisation of rock and multiphase properties (Pini and Benson, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…the scale at which all reservoir processes operate) (Shafer, 2013). Most significantly, such developments have revealed that results must be interpreted by acknowledging the fact that capillary pressure heterogeneity results into local saturation development (Graue, 1994;Chaouche et al, 1994;Shi et al, 2011;Pini et al, 2012;Alemu et al, 2013;Oh et al, 2015;Ott et al, 2015), which may lead to apparent flow rate effects on macroscopic properties of relative permeability and residual trapping (Perrin and Benson, 2010;Krevor et al, 2011;Kuo and Benson, 2015;Reynolds and Krevor, 2015). Accordingly, improved laboratory workflows are now being developed that make use of such wealth of information by e.g., referring to the internal structure of the sample and in-situ observations, to obtain accurate parameterisation of rock and multiphase properties (Pini and Benson, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…A lower density scCO 2 bubble sitting below higher density water leads to the water having a higher pressure at the bottom of the scCO 2 than the top and this difference creates a force gradient that pushes the scCO 2 upwards. Numerous field and numerical studies have shown that buoyancy forces can play a critical role in the vertical flow of scCO 2 [7,10,32,39].…”
Section: Flow: Supercritical Co 2 Simulationsmentioning
confidence: 99%
“…(2009), and Oh et al. (2015) studied the effect of heterogeneity on capillary trapping, ignoring dissolution. Other authors (Doughty & Pruess, 2004; Doughty et al., 2001; Gershenzon, Ritzi, et al., 2015) have only analyzed dissolution trapping in a few idealized depositional settings.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of permeability stratification during the injection of CO 2(g) in GCS has been observed in several works, which have demonstrated that, after injection, a major proportion of CO 2 -rich phase can enter and move preferentially through relatively high permeability conduits or channels, creating erratic patterns (Chadwick & Noy, 2010;McGuire et al, 1995;Obi & Blunt, 2006;Oh et al, 2015;Rasmusson et al, 2015;Stalkup & Crane, 1994;Tsang et al, 2001). Data from Sleipner field site (Gregersen, 1998) in the North Sea, which is a reservoir formed by interbedded sandstones and mudstones, indicated that the injected CO 2(g) was mostly present in several disconnected layers of relatively high permeability with a thickness of about 10 m (Chadwick et al, 2004(Chadwick et al, , 2005.…”
mentioning
confidence: 99%